Utilizing Artificial Intelligence to Enhancing the Effectiveness of Energy Systems: Challenges and Future Chances (Comprehensive Journal of Science, 2025)
Energy systems are considered an essential part of supporting economic growth and sustainable development; therefore, the demand for energy management systems is expected to increase significantly in the coming years. Furthermore, energy systems face numerous challenges, including the massive amount of data, difficulties in integrating modern technologies with traditional methods, technical problems, and a shortage of experts in artificial intelligence and security, among others.    However, there are promising future prospects for employing artificial intelligence technologies to improve the efficiency of energy systems, including enabling prediction, integrating modern technologies with renewable energy management, and developing grid systems. This research aims to identify the challenges and opportunities for using artificial intelligence in energy system management, explore the most widely used applications and technologies in this field, and integrate AI technologies into energy systems. The research employed a descriptive analytical approach by reviewing previous studies and conducting interviews with experts in the fields of energy systems and artificial intelligence technologies at the research center of Al-Zawia University. The study also includes a successful analysis of artificial intelligence projects. The research recommendations included training programs in artificial intelligence, improving research, enhancing data collection, and encouraging public-private partnerships to achieve the objectives.
Keywords: Artificial Intelligence (AI) , Effectiveness , Energy Systems, Challenges, Future Chances.